PENGARUH REWARD TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (Studi Pada Karyawan PT Bank Central Asia Tbk. Cabang Utama Surakarta) - Fausta Hindarti & Amin Wahyudi (Universitas Slamet Riyadi, 2016)
This research aims to analyses (1) significance effect of reward on employee job satisfaction (2) significance effect of reward on employee motivation (3) significance effect of motivation on employee job satisfaction (4) the effect of reward on employee job satisfaction, through motivation as the mediating variable. The location of this research at PT Bank Central Asia Tbk Main Branch in Surakarta. This research using samples of 100 employee with proportional random sampling technique. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis using path analysis. The result shows that (1) reward has not significance effect on employee job satisfaction, thus hypothesis 1 rejected. (2) reward has significance effect on employee motivation, thus hypothesis 2 supported. (3) motivation has significance effect on employee job satisfaction, thus hypothesis 3 supported. (4) motivation as the mediating variable of the effect reward on employee job satisfaction, thus hypothesis 4 supported. Increased of employee job satisfaction can be used as a strategy to build a service excellence for the company in PT Bank Central Asia Tbk. Main Branch Surakarta. Employee job satisfaction can be improved through the rewards that can motivate employees to work more productively and professionally. Keywords: reward, motivation, job satisfaction